2010
DOI: 10.1515/jpem.2010.054
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, Physical Activity and Blood Lipid Profile in 13-year-old Adolescents

Abstract: The main aim of this study was to determine the extent to which physical activity and adiposity are associated with blood cholesterol levels in male adolescents. Anthropometric and physical fitness values were measured in all children. Body mass index (BMI) and physical activity index (PAI) were used to split participants into active overweight (ACO) and non-active normal-weight (NAN) groups. The cutoffs for the ACO group were BMI ≥ 22.6 kg/m 2 and PAI ≥ 3.5, respectively, whereas the corresponding cutoffs for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
4
9
0
3
Order By: Relevance
“…It is well known that being physically active and having higher levels of cardiorespiratory fitness benefit health, functional ability, quality of life, and longevity [16,17]. Furthermore, a recent metaanalysis showed that children who participated in exercise interventions presented significant reductions in BMI, waist circumference, and %FM as well as increases in cardiorespiratory fitness, lower-body strength, and speed-agility compared to controls [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that being physically active and having higher levels of cardiorespiratory fitness benefit health, functional ability, quality of life, and longevity [16,17]. Furthermore, a recent metaanalysis showed that children who participated in exercise interventions presented significant reductions in BMI, waist circumference, and %FM as well as increases in cardiorespiratory fitness, lower-body strength, and speed-agility compared to controls [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent metaanalysis showed that children who participated in exercise interventions presented significant reductions in BMI, waist circumference, and %FM as well as increases in cardiorespiratory fitness, lower-body strength, and speed-agility compared to controls [18]. Additionally, adolescents who are physically active present higher levels of cardiovascular fitness, a better blood lipid profile, and lower body adiposity [16]. Overall, evidence seems to indicate that being physically active during adolescence can minimize these various health risks [19].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has shown to be effective in improving cholesterol levels in adolescents (22). We have determined that higher overall physical activity is associated with lower non-HDL cholesterol, independent of anthropometry category.…”
Section: Physical Activity Interacts With Anthropometry In the Associmentioning
confidence: 89%
“…Contrary to the many benefits, the physical activity of children of all ages is constantly decreasing (Bornstein, Beets, Byun, & McIver, 2011;Konstabel et al, 2014), and consequently the HRF Ostojić, O`Neil, Calleja, Terrados, & Stojanović, 2010;Ostojić, Stojanović., Stojanović, &, Marić, 2010;Ostojić, Stojanović, Stojanović, Marić, & Njaradi, 2011;Đordjić et al, 2016).…”
Section: Introductionmentioning
confidence: 99%